Impact Assessment on House Reconstruction of Two Funding Systems - Alvaappillai, P.; Prabhaharan, M.; Mikunthan, T. (JUICE- 2012 University of Jaffna, 2012)
Two systems of multimillion financially supported reconstruction projects were practiced in Vadamaradchi North to improve the condition of affected people those who have been facing continuous grievances for a long period nearly three decades of improper ground situation the years indicating 1980-1981, 1986-1987, 1992-1993, 1996-1997, 2004-2005 and 2008-2009. The two systems were evaluated after five years of completion of house reconstruction with settlement that is the “Core House Concept” (CHC) known as House Owners Reconstruction System (HORS) supporting direct financial system and Finished House Reconstruction System (FHRS) supporting indirect financial and material transaction including land allotment, a cluster housing project. The above two systems were evaluated after construction of houses, the HORS done by NEHRP under world bank and FHRS done by NGO known as HUDEC CARITAS. Evaluation was carried out on the basis of 12 levels of house reconstruction performance chart (HRPC), three economical aspects, two social aspects and two financial aspects in the coastal area of Vadamaradchi, Alvai North -West the most affected coastal village was selected for the impact assessment. Visited house by house for this study and selected 121 houses built under World Bank (NEHRP-HORS) and 45 houses built under the FHRS, LNGO/CARITAS. An initial study was conducted for the last five months that revealed the FHRS indicated several benefits without any financial or material flow impediments but HORS indicated large number of unidentified financial transaction, material usages, confusion in selection of beneficiaries, contradiction among vulnerable people in finding location, improper time consuming activities, abundant houses, looted houses, less quality building materials, unidentified beneficiaries, false statement in handling money in field, cheating money transaction, deduction in money handling and facilitated losses in funding installment. It is obviously identified FHRS is more effective system and the other world bank HORS is utterly failed particularly in this area, even though affected people got their houses and satisfied, an acceptable result.
Keywords: Beneficiaries; Reconstruction; NEHRP; CARITAS